Self-Assembled Human Adipose-Derived Stem Cell-Derived Extracellular Vesicle-Functionalized Biotin-Doped Polypyrrole Titanium with Long-Term Stability and Potential Osteoinductive Ability - Chen, Lifeng; Mou, Shan; Li, Fangying; Zeng, Yuyang; Sun, Yang; Horch, Raymund E.; Wei, Wei; Wang, Zhenxing; Sun, Jiaming (ACS Applied Materials and Interfaces, 2019)
Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs), containing proteins or microRNAs (miRNAs), possessing various biological activity and low immunogenicity, are considered promising for surface modification of bone grafts. However, the modification efficiency is not satisfied yet, resulting in compromised therapy effects. Here, we report a novel immobilized method by self-assembling biotinylated MSC-EVs onto the surface of biotin-doped polypyrrole titanium (Bio-Ppy-Ti) to improve its biofunctions in vitro and in vivo. Using this method, the amount of human adipose-derived stem cell-EVs (hASC-EVs) anchored onto the Bio-Ppy-Ti surface was 185-fold higher than that of pure Ti after ultrasonic concussion for 30 s and it remained stable on the Bio-Ppy-Ti surface for 14 days at 4 °C. Compared to pristine Ti, EV-Bio-Ppy-Ti exhibited enhanced cell compatibility and osteoinductivity for osteoblasts in vitro and anti-apoptosis ability in the ectopic bone formation mode. Gene chip analysis further demonstrated that several osteoinductive miRNAs were encapsulated in hASC-EVs, which may explain the high bone regeneration ability of EV-Bio-Ppy-Ti. Thus, this MSC-EV biotin-immobilized method appears to be highly efficient and long-term stable for bone graft bioactive modification, demonstrating its potential for clinical metal implants.
CRIS-Team Scopus Importer:2019-12-13
Keywords: adipose stem cell-derived extracellular vesicles; biotin-streptavidin complex; osteoinductivity; polypyrrole; surface modification